Greener Transport Connectivity for Eastern Partnership Countries - World Bank (World Bank, Washington, DC, 2020)
The Eastern Partnership (EaP) is a joint policy initiative, which aims to deepen and strengthen relations between the European Union (EU) and its six Eastern neighbours. One of its four priority areas is stronger connectivity which includes the extension of the Trans European Transport Network (TEN-T) to the EaP region. On the policy front, it aims at achieving regulatory convergence across transport modes between member countries and with the EU to heighten the focus on energy efficiency and combat climate change. The EaP countries experienced a large shock to their economies following the end of the Soviet Union in 1989. At the same time, EaP countries are acutely aware of the need to converge with the EU in terms of energy efficiency, environment and climate change goals. The EU is currently formalising its European Green Deal, which is a roadmap for making the EU's economy sustainable. The objective of this study is to assist decision-makers in prioritizing strategic transport policies and infrastructure investments. It develops the evidence base and prioritisation framework for improving the transport sector of the region including improved energy efficiency and sustainability so that it is not left behind by advances in the EU. The study has also developed an online visualization tool to help policy makers explore and use the results of the modelling exercise.